Pelatihan Pemeliharaan Pedet dan Pembuatan Pakan Ternak Asal Limbah Sawit di Desa Tanjung Pasar Kecamatan Muara Pawan Kabupaten Ketapang - Warsito, Sunaryo Hadi; Lamid, Mirni; Hidayatik, Nanik; Hermadi , Herry Agoes; Hidanah, Sri; Lokapirnasari, Widya Paramita; Al-Arif , M. Anam; Sabdoningrum, Emy Koestanti; Rosyada, Zulfi Nur Amrina (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem of livestock farmers in Tanjung Pasar Village, Muara Pawan District, Ketapang Regency, West Kalimantan is the high number of calf deaths and the use of palm oil waste in the form of palm oil mud which is abundant in the area which is directly given to livestock, even though the nutritional content in it is quite low when used as a source of feed to meet the needs of life in cattle. So the urgency of this problem is the need to increase the knowledge of livestock farmers regarding how to intensively raise calves in order to reduce high mortality in calves and increase the knowledge of livestock farmers regarding how to process animal feed from palm oil mud. Palm oil mud processing can be done to increase its nutrition. Therefore, the Community Service team from the Faculty of Veterinary Medicine, Airlangga University has carried out activities to improve the knowledge and skills of breeders in maintaining calves properly and processing palm oil mud. The specific output targets achieved are in the form of increasing the ability of farmers to raise calves better and make feed from palm oil mud, so that the health of calves can improve and the nutritional needs of the livestock will be met. The method used in achieving these goals is through activities that include counseling and training on how to rearing of calves, making animal feed from palm oil waste through fermentation methods and making mineral blocks. The results that have been achieved are in the form of a level of knowledge and understanding of how to rearing of calves which has increased from the previous 15.38% to 96.15%. Likewise, how to make animal feed from 11.54% to 96.15%, and how to make mineral blocks from 11.54% to 96.15%.